Analysis of base pressure control with ribs at Mach 1.2 using CFD method - Ahmad Fakhruddin, Ahmad ‘Afy; Mahboobali, Fharukh Ahmed Ghasi; Khan, Ambareen; Akhtar, Mohammad Nishat; Khan, Sher Afghan; Pathan, Khizar Ahmed (SEMARAK ILMU PUBLISHING, 2024)
This paper discusses the control of base pressure by passive means, where the jet is issued from a converging nozzle at sonic Mach number under a favorable pressure gradient. The effect of employing annular ribs on the enlarged duct and its impact on the flow field, as the passive control mechanism from a converging nozzle at the sonic Mach number, is investigated numerically in this study. The velocity distribution and base pressure changes are analyzed using a numerical compressible turbulence flow model. Initially, the rib is positioned at 16 mm (1D) from the base of the duct. Later, the rib position is shifted from 1D to 2D and then to 3D and 4D. The effect of variation of the rib positions, as well as its height from 1 mm to 3 mm, keeping the width of the rib fixed to 3 mm, is studied. The nozzle pressure ratio varies from 1.5 to 5, and the rib location is 1D and 2D. The velocity variation in the duct with and without rib placement is also analyzed. The results revealed comprehensive spread observations from the positive analysis of base pressure variation in ducts with no ribs and ribs with heights of 1 mm and 2 mm. The base pressure increased significantly with increasing nozzle pressure ratio for both rib heights compared to a smooth duct. It is also deduced that the highest base pressure is achieved at an aspect ratio of 3:1 when placed at 4D.